2006
DOI: 10.4049/jimmunol.176.6.3557
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 and IL-13 Form a Negative Feedback Circuit with Surfactant Protein-D in the Allergic Airway Response

Abstract: The innate immune molecule surfactant protein-D (SP-D) plays an important regulatory role in the allergic airway response. In this study, we demonstrate that mice sensitized and challenged with either Aspergillus fumigatus (Af) or OVA have increased SP-D levels in their lung. SP-D mRNA and protein levels in the lung also increased in response to either rIL-4 or rIL-13 treatment. Type II alveolar epithelial cell expression of IL-4Rs in mice sensitized and challenged with Af, and in vitro induction of SP-D mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(133 citation statements)
references
References 62 publications
4
128
1
Order By: Relevance
“…46 We have previously shown that the lung collectin SP-D has immunosuppressive activities 15 and that it protects against inflammatory changes of the lung. 40 In this study we investigated the regulatory link between these innate immune molecules.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…46 We have previously shown that the lung collectin SP-D has immunosuppressive activities 15 and that it protects against inflammatory changes of the lung. 40 In this study we investigated the regulatory link between these innate immune molecules.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Our previous studies in SP-D −/− mice also demonstrated the presence of activated CD3/CD4 + T cells in the airway submucosal tissue with strikingly increased levels of thymus and activation-regulated chemokine, a chemokine responsible for attracting T H 2 and dendritic cells. 15 These findings suggested that in addition to macrophages, dendritic cells also might be affected by a lack of SP-D and that this lung collectin might have an essential role in maintaining immune homeostasis in the lung under normal, noninflammatory circumstances.…”
Section: Tnf; Sp-d; Dendritic Cell; Mouse Model; Airway Inflammationmentioning
confidence: 97%
See 3 more Smart Citations